Gender Ideology in The Diary Of Adam And Eve by Mark Twain - Ayuningtyas, Paramita (Humaniora, 2011)
This article aims to show that behind the new version of Genesis by Mark Twain in his novel The Diary of Adam and Eve, there are some patriarchal principles that appear in it. It can be seen from the characterizations of Adam and Eve. By using some concepts from feminism and also focusing on the context of the novel, the analysis shows that patriarchal stereotypes about gender are applied in constructing the characters of Adam and Eve. Not only the content, but the form of the diary is also analyzed with the same method, and the same result is found. Therefore, it can be concluded that in spite of his progressiveness, Mark Twain still held patriarchal values in re-interpreting the tale of human creation.